Exploring Culinary as a Tourist Attraction in Takengon, Central Aceh - Astuti, Widya (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2024)
The objective of this research is to explore and analyze how the tourists’ perception of cuisine in Takengon. Using descriptive qualitative study and taking the data through observation and interviews to conduct the research, it was found that central Aceh has a variety of food and drinks which had become a potential attraction for tourists to visit. A variety of coffees, Masam jing, Gutel, Cecah, Pengat, and Lepat have contributed to the increasing number of tourists visiting Takengon since the culinary become one of their reasons to come. Moreover, such perceptions are expected to be useful for food and drink development and innovation in Gayo high land.